An account of human dignity able to entail dignity for the severely mentally disabled, inspired by sub-Saharan African thought - Koali, Seeiso Jonas (My University, 2015)
This research report evaluates different conceptions of human dignity with a view to articulate a more plausible and attractive account that allows for the recognition of the dignity of severely mentally disabled people. Many of the existing conceptions of human dignity inevitably exclude the severely mentally disabled. Attention is given to the dominant Kantian conception of dignity as well as to sub-Saharan African notions. In this research, I articulate and critically defend the most attractive and plausible aspects of sub-Saharan African thought that can contribute to the development of an attractive and plausible account of human dignity that will recognize the dignity of severely mentally disabled people. In order to fulfill this aim, I address the following question: What would a plausible and attractive account of human dignity that is able to recognize the dignity of severely mentally disabled people look like? This research report argues that the theoretical resources for a more inclusive and attractive conception of human dignity can be found in sub-Saharan thought, and that can also contribute to the growing realization that African philosophy has a valuable contribution to make to the enrichment of our ethical (and particularly, bioethical) reasoning and discourse. This study is purely normative. Data was not collected, and there was no involvement of research participants.
MSc Med (Bioethics & Health Law